Analysis of the Performance of Non-Metallic Mineral and Rock Tax Collection in Increasing Regional Original Revenue (PAD) in East Lombok Regency - Khairul Hadi; Abdul Manan; Siti Sriningsih (Tinta Emas Institute, 2024)
This research is quantitative descriptive research, which is a quantitative descriptive method is a research method that describes or explains data through numbers. The data in this study are primary data and secondary data. Primary data obtained from interviews with Bapenda employees of East Lombok Regency while secondary data comes from related agencies. The results of this study found that the growth rate of non-metal mineral and rock tax is included in the criteria less successful. The effectiveness of non-metal mineral and rock taxes meets the criteria of less. The contribution of non-metallic mineral and rock tax is included in the criteria very less and the elasticity of non-metallic mineral and rock tax is included in the elastic criteria.